Re-thinking the Approach to Informal Businesses : Typologies, Evidence and Future Exploration - Nielsen, William Iver; Marusic, Andreja; Ghossein, Tania; Solf, Sylvia (World Bank, Washington, DC, 2020)
Interventions over the past decades to encourage increased business formalization have shown mixed results and produced limited knowledge on how to address informality systematically. The scale of the informal sector in emerging and developing economies, which accounts for 25 to 40 percent of GDP and often more than 60 percent of employment, merits rethinking approaches to formalization. Based on a review of relevant literature on informality and efforts to promote formalization, this paper will discuss the use of the term “informality” to align with the heterogeneity that exists within the informal sector and to identify factors that drive formality. From there, the paper proposes four specific areas for additional research and pilot interventions: (1) supporting informal clusters; (2) providing support to informal businesses without formalization as a target; (3) developing simplified, intermediate, and temporary legal statuses for informal businesses to better align with business needs and government goals; and (4) understanding behavioral insights that influence businesses’ decisions to remain informal and that can contribute to effective policy making. Throughout this discussion, the authors aim to motivate development and testing of new approaches to informality based on a deepened understanding of the needs of informal businesses.